2012
DOI: 10.1111/tpj.12014
|View full text |Cite
|
Sign up to set email alerts
|

SIZ1 deficiency causes reduced stomatal aperture and enhanced drought tolerance via controlling salicylic acid‐induced accumulation of reactive oxygen species in Arabidopsis

Abstract: SUMMARYTranspiration and gas exchange occur through stomata. Thus, the control of stomatal aperture is important for the efficiency and regulation of water use, and for the response to drought. Here, we demonstrate that SIZ1-mediated endogenous salicylic acid (SA) accumulation plays an important role in stomatal closure and drought tolerance. siz1 reduced stomatal apertures. The reduced stomatal apertures of siz1 were inhibited by the application of peroxidase inhibitors, salicylhydroxamic acid and azide, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
147
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(158 citation statements)
references
References 92 publications
(184 reference statements)
10
147
0
1
Order By: Relevance
“…These studies above mentioned demonstrated that the endogenous SA level is a plastic response due to it is modified according to organ, ontogenetic stage, particular species and type of stress. Moreover, [51] informed that SA accumulation may play a protective role during water stress through the regulation of SA-inducible PR1 and PR2 genes. Nevertheless, some studies showed that the SA accumulation aggravated the salinity negative effects.…”
Section: Effect Of Sa On Plant Growth Responses Under Drought and Salmentioning
confidence: 99%
“…These studies above mentioned demonstrated that the endogenous SA level is a plastic response due to it is modified according to organ, ontogenetic stage, particular species and type of stress. Moreover, [51] informed that SA accumulation may play a protective role during water stress through the regulation of SA-inducible PR1 and PR2 genes. Nevertheless, some studies showed that the SA accumulation aggravated the salinity negative effects.…”
Section: Effect Of Sa On Plant Growth Responses Under Drought and Salmentioning
confidence: 99%
“…Increased total SA content was also reported in the leaves and roots of barley, when drought stress preceded UV-B radiation (Bandurska and Cieslak, 2012). The increased SA content may be responsible for the observed alleviating an Arabidopsis SUMO E3 ligase, caused reduced stomatal aperture and enhanced drought tolerance via controlling SA-induced accumulation of reactive oxygen species (Miura et al, 2013). As the control of stomatal aperture is important for efficiency and regulation of water use and for the response to drought, UV-B stress-induced SA accumulation could have positive effect in PEG-treated plants.…”
mentioning
confidence: 99%
“…In other SA-accumulating mutants, cpr5 and acd6, ROS was accumulated in guard cells, light-induced stomatal opening was impaired, and drought tolerance was enhanced. 6 These results suggest that SA accumulation induces ROS accumulation, resulting in inhibition of light-induced stomatal opening. However, it is to be clarified whether transpirational water loss is suppressed in the cpr5 and acd6 mutants and whether ROS production mediated by peroxidases is involved in the inhibition of light-induced stomatal opening in the cpr5 and acd6 mutants.…”
mentioning
confidence: 66%
“…[3][4][5] Reactive oxygen species (ROS) levels in siz1 guard cells are higher than those in the wild-type guard cells and light-induced stomatal opening was inhibited by the siz1 mutation, reducing water loss and enhancing drought tolerance. 6 These phenotypes are suppressed by introduction of nahG gene, which encodes a salicylate hydroxylase that catalyzes the conversion of SA to catechol, into the siz1 mutant. Peroxidase inhibitors, salicylhydroxamic acid (SHAM) and azide, suppressed the inhibition of light-induced stomatal opening in the siz1 mutant, suggesting that ROS production mediated by peroxidases is involved in the inhibition of stomatal opening.…”
mentioning
confidence: 99%